Effectiveness of The Performance Appraisal System of Functional Officials With Employee Work Targets at The Health Department of Southeast Sulawesi Province - Sartini Risky; Waode Nova Noviyanti Rachman; Sri Mulyani; Lodes Hadju; Firmansyah Firmansyah (YCAB Publisher, 2026)
Background: The Employee Performance Objectives system represents a major reform in Indonesia’s civil service appraisal mechanism, yet its effectiveness depends on regulatory understanding, digital literacy, and evaluator competence. Objective: To assess the effectiveness of the functional officials’ performance appraisal system at the Southeast Sulawesi Provincial Health Office based on input, process, and output components. Methods: A qualitative evaluative case study was conducted with eight purposively selected informants. Data were collected through in-depth interviews and analyzed using NVivo through coding, categorization, and thematic interpretation. Results: The employee performance objectives system is perceived as more practical and flexible than the previous DUPAK system. However, challenges include limited understanding of new regulations, low digital literacy, inconsistent socialization, and the absence of structured performance dialogue. Monitoring features are available but not optimally used. Despite procedural weaknesses, the new system increases employee motivation and encourages better documentation, although assessment objectivity remains limited. Conclusion: The appraisal system shows progress in efficiency and alignment with regulations but still requires improvement in evaluator capacity, regulatory comprehension, monitoring, and feedback mechanisms. Strengthening digital skills and structured communication is essential for achieving a more objective and effective performance appraisal system.